Índice álgico e qualidade de vida em pacientes com distúrbio osteometabólico submetidos a terapia renal substitutiva - Prado, Lindaura da Silva (2018)
Renal failure is characterized by loss of kidney function. During the course of the disease, mostpatients develop the mineral and bone disorder of chronic kidney disease (CKD-BMD). The early identification of the clinical manifestations allows conducts to be performed to minimize bone pain and improve the functional capacity, bringing to patients affected by this pathology a better quality of life. For this reason, this study aimed to evaluate pain index in patients with osteometabolic disorder of chronic kidney disease, submitted to hemodialysis, and its impact on the quality of life. An observational, epidemiological cross-sectional epidemiological study was conducted with a sample of 195 patients submitted to hemodialysis. Biochemical parameters associated to bone metabolism were evaluated, such as: Calcium, phosphorus, PTH, alkaline phosphatase, calcitriol and aluminum. The qualification and quantification of pain was measured using the questionnaires: Brief Pain Inventory (IBD) and McGill, respectively. The evaluation of patients' quality of life was performed using the Quality of Life Questionnaire in Renal Disease (KDQOL-SF). This study was approved by CEP / UFS under the number of CAAE: 60158216.6.0000.5546. Of the total number of patients, 37.44% presented altered values for calcium. Concerning phosphorus, approximately 50% of the patients presented alterations below or above the reference values. Of the total, 17.44% of the volunteers presented the product of calcium and phosphorus levels ≥ 55 mg / dL. As for PTH, 74.87% of the patients presented values above or below the reference range. Evaluating calcitriol and alkaline phosphatase, it was observed that 34.36% and 45.65% of the patients presented serum levels outside the reference levels, respectively. From these data, 104 (53.33%) patients were classified as having BMD. Black patients had a higher risk (RR = 1.36) for developing the disorder. In addition, longer treatment times also showed a relationship with the development of BMD. It was also verified the high prevalence of patients with BMD, especially BMD with high remodeling. Through the use of IBD, it was possible to observe that 66 patients (33.85%) had experienced pain in the last 24 hours, with a mean pain score of 4.59 ± 2.33. Patients with musculoskeletal pain had high levels of alkaline phosphatase. In general, these pain conditions impacted on general activity, mood, walking ability and sleep. Through the McGill questionnaire, 109 patients (55.90%) reported experiencing pain, of which 38 (19.49%) reported pain at the time of interview, ranging from weak to unbearable. The sensorial and affective dimensions had a higher index of pain classification. The mean total quality of life score of patients with CKD was 64.72%, being an intermediate quality of life index. Only the status of work had a high impact on the quality of life of patients submitted to hemodialysis. Evaluating the pain dimension, it can be observed that patients with present BMD present lower quality of life. Through this study it was possible to verify that more than half of the patients on hemodialysis reported pain, varying from weak to unbearable, with a higher prevalence for mild and moderate pain, with emphasis on sensory and affective dimensions. In addition, although patients presented a mean total quality of life intermediate score, pain has a significant impact on the quality of life of BMD patients indicating that this disorder aggravates the patient's clinical condition.